1992
DOI: 10.1097/00000658-199209000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Strictures Complicating Liver Transplantation Incidence, Pathogenesis, Management, and Outcome

Abstract: Six hundred sixty-six patients received 792 liver transplants between February 1, 1984 and September 30, 1991. Biliary reconstruction was by choledochocholedochostomy (CDCD) with T-tube (n = 509) or Roux-en-Y choledochojejunostomy (CDJ) (n = 283). Twenty-five patients (4%) developed biliary strictures. Anastomotic strictures were more common after CDJ (n = 10, 3.5%) than for CDCD (n = 3, 0.6%). Intrahepatic strictures developed in 12 patients. Six patients had occult hepatic artery thrombosis (HAT). The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
3
8

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(188 citation statements)
references
References 15 publications
5
172
3
8
Order By: Relevance
“…Some authors have observed no association between IBL and chronic rejection [4]. However, others suggest that chronic rejection is associated with chronic obliterative arteriopathy, and it has been postulated that the resulting bile duct ischemia may lead to duct loss and biliary stricture [14].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have observed no association between IBL and chronic rejection [4]. However, others suggest that chronic rejection is associated with chronic obliterative arteriopathy, and it has been postulated that the resulting bile duct ischemia may lead to duct loss and biliary stricture [14].…”
Section: Discussionmentioning
confidence: 99%
“…The involved etiological factors seems to be the small bile duct diameter, a big disproportion between graft and recipient bile ducts, the ischemia time, tension on the anastomosis, infection and other technical issues (8) . On the other hand, ischemia related to hepatic artery problems seems to be more related to the occurrence of NABS (2,13) . NABS can present as a single or multiple stenosis and has a reserved prognosis when compared to ABS (18) .…”
Section: Discussionmentioning
confidence: 95%
“…Anastomotic strictures are usually easier to treat than intrahepatic lesions. Early nonanastomotic strictures demonstrate higher success rates than strictures appearing later than three months after LT [41][42][43]. Endoscopic and transhepatic treatment options are limited in patients with impaired liver function similarly to the diagnostic procedure.…”
Section: Endoscopic and Transhepatic Treatmentmentioning
confidence: 99%
“…In spite of encouraging progress in interventional non-surgical ITBL-treatment, and achievements in graft resection, up to 50% of patients with non-anastomotic strictures still require re-transplantation of the liver [30,43,47,48]. Re-transplantation of the liver is supposed to be the definitive therapy of graft damage being the last resort of therapeutical options.…”
Section: Re-transplantationmentioning
confidence: 99%
See 1 more Smart Citation